A kind of silk protein composite hydroxyapatite microsphere filler for injection and preparation method thereof
Silk proteins of different molecular weights were screened through AI algorithms, and the hydrophobic interaction was used to induce the silk protein to form a β-fold structure. Combined with layer-by-layer self-assembly technology to improve the dispersion of hydroxyapatite microspheres, solving the problems of filler toxicity and uneven dispersion of microspheres in the prior art, achieving safe and efficient medical beauty filling effect.
Patent Information
- Application Number
- CN202410700762.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-31
AI Technical Summary
In existing medical beauty fillers, the addition of crosslinking agents will increase toxicity, leading to local tissue reactions, and the gelation rate of silk proteins is slow, making it difficult to accurately determine silk proteins of different molecular weights, and the microspheres are unevenly dispersed in the gel matrix.
Silk proteins of different molecular weights were screened through the AI algorithm combining the rheological properties of silk proteins. The hydrophobic interaction between hydroxypropyl methyl cellulose or carboxymethyl cellulose and silk protein molecules after heating induces the silk protein molecular chain from random curling to β-sheet, forming a small and uniform β-sheet structure, which is uniformly distributed throughout the gel system as crosslinking sites. At the same time, the surface of hydroxyapatite microspheres is encapsulated by layer-by-layer self-assembly to increase their surface hydrophilicity, and stir and defoam with the silk protein-cellulose gel with negative pressure. The injection gel prepared has excellent mechanical properties and good dispersion of microspheres.
The safety and versatility of silk protein composite hydroxyapatite microsphere filler is achieved, the use of chemical crosslinking agents is avoided, the toxicity of the filler is reduced, the dispersion and filling effect of the microspheres in the gel matrix is improved, and different needs for beauty are met.
Smart Images

Figure CN118924948B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical cosmetic surgery, and in particular, relates to a method for preparing a silk protein composite hydroxyapatite microsphere injection filler with different molecular weights. Background Art
[0002] In recent years, injectable gels used for medical cosmetic fillers have developed rapidly. By increasing the cross-linking degree of hyaluronic acid, the degradation time of the injectable can be prolonged and its elastic modulus can be increased. It is suitable for different filling sites, such as tear grooves, crow's feet and other sites that require superficial filling, temples, noses, chins and other sites that require medium-depth filling, and nasolabial folds, corners of the mouth, forehead and temporal areas and other sites that require deep filling. Patent CN116284886A establishes a multi-cross-linked gel system to increase stability and viscoelasticity, but the addition of cross-linking agents will increase the toxicity of the injectable and induce local tissue reactions. Therefore, there is an urgent need for a material with higher biosafety to meet different aesthetic needs.
[0003] As an ideal natural polymer material, silk protein has the advantages of extremely low immunogenicity, good biocompatibility, and the advantage of promoting collagen regeneration. It is often used in tissue engineering, soft tissue repair, wound repair and other fields. Silk proteins with different molecular weights have different elastic moduli and complex viscosities, different degradation cycles, and different applicable filling locations and depths. However, silk protein gel as a filler also has problems that need to be overcome: 1. It is difficult to accurately measure silk proteins with different molecular weights; 2. The slow gelation rate of silk protein makes it very easy for the initial contamination bacteria of silk protein gel to exceed the standard, so it needs to be gelled quickly to adapt to large-scale production.
[0004] Hydroxyapatite is the main inorganic component of human and animal bones. Its metabolites are calcium ions and phosphate ions, which are common in the human body. It has good biocompatibility. Mixing hydroxyapatite microspheres with silk protein-cellulose gel is conducive to achieving continuous collagen in situ regeneration. Patent CN116808290A prolongs the shelf life by dry powdering the filler after mixing gel and microspheres, but it is difficult to disperse the microspheres evenly in the gel matrix after re-dissolving, and it is inconvenient to use. The steps are relatively cumbersome, which increases the difficulty of doctors during the operation. Patent CN117919515A mixes binormally distributed microspheres with gel matrix to make it have good injectability and shape plasticity, but the small-sized microspheres (1-10 microns) are easy to trigger macrophage storms and produce the risk of granulomas. A safer way is needed to mix hydroxyapatite microspheres and gel matrix evenly. Summary of the invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a method for preparing a silk protein composite hydroxyapatite microsphere filler with different molecular weights and a narrow molecular weight distribution. In order to ensure the safety of the filler while meeting various beauty needs and being suitable for various filling parts, the present invention proposes to screen out silk proteins with different molecular weights by combining the rheological properties of silk proteins through an AI algorithm. The silk proteins have different elastic moduli and complex viscosities, and different degradation cycles, and are suitable for different filling parts and depths. A new type of silk protein composite hydroxyapatite microsphere filler was developed through a simple method of mixing and heating. After heating, the hydrophobic interaction between hydroxycellulose or carboxyl cellulose, such as hydroxypropyl methylcellulose or hydroxypropyl cellulose or carboxymethyl cellulose, hydroxyethyl cellulose and silk protein molecules induced the silk protein molecular chain from random curling to β-folding. This secondary structural transformation allows small and uniform β-folding structures to form inside the silk protein, and it is these β-folding structures that serve as cross-linking sites and are uniformly distributed throughout the hydrogel. This simple and effective method avoids the use of chemical cross-linking agents and improves the safety of the filler. Silk protein and cellulose are wrapped on the surface of hydroxyapatite microspheres by layer-by-layer self-assembly to increase their surface hydrophilicity, and then the hydroxyapatite microspheres and silk-cellulose gel are degassed by negative pressure stirring. The prepared injectable gel has excellent mechanical properties, good microsphere dispersibility, and is easy to extrude.
[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a silk protein composite hydroxyapatite microsphere filler for injection, and the mixed gel includes the following components: silk protein-cellulose gel, modified hydroxyapatite microspheres, an osmotic pressure regulator, and water for injection.
[0007] Preferably, the silk protein-cellulose gel comprises silk protein-hydroxypropyl methylcellulose and silk protein-carboxymethyl cellulose.
[0008] Preferably, the method for preparing the silk protein-cellulose gel specifically comprises the following steps:
[0009] S1: Preparation of silk protein solution: The degummed silk is dissolved and purified to obtain silk protein, and silk proteins of different molecular weights are screened out through membranes with different molecular weight cut-offs;
[0010] S2: Physical gelation of silk protein: dissolving the physical crosslinking agent in water to fully swell, adding hydroxy cellulose or carboxyl cellulose or corresponding derivative aqueous solution to the silk protein aqueous solution prepared in step S1, adjusting the osmotic pressure, and then stirring the mixed solution evenly, and placing it in an oven for gelation;
[0011] S3: Preparation of hydroxyapatite microspheres modified by layer-by-layer self-assembly: Disperse the hydroxyapatite microspheres in the silk protein solution prepared in step S1, stir at room temperature, then take out the microspheres and dry them; then dissolve them in the cellulose solution, stir at room temperature, then take out the microspheres and dry them; repeat 3 to 5 times;
[0012] S4: Preparation of silk protein composite hydroxyapatite microsphere filler for injection: degassing the modified hydroxyapatite microspheres and silk protein-cellulose gel by negative pressure stirring, sterilizing them with high pressure steam, and aseptically filling them in a prefilled syringe to obtain a silk protein composite hydroxyapatite microsphere filler for injection;
[0013] Furthermore,
[0014] S1: Preparation and determination of silk proteins with different molecular weights: Silk protein is prepared from mulberry silk through the steps of degumming, dissolution, purification and desalination. The silk protein is dissolved in ionic liquid and tested on a MCR301 rotational rheometer. The data curves at multiple test temperatures are measured respectively. The data are then modeled using the rouse model, and the physical parameters required for the model are measured. The nonlinear model is then fitted using an AI algorithm to obtain molecular weight data, and the molecular weight of the silk protein is calculated using the fitting parameters.
[0015] Among them, referring to Appendix B of the industry standard "Silk Protein for Tissue Engineering Medical Devices" which is currently being publicized, the measured rheological data and viscosity data were imported into Favorsun SmartMolFit "Fully Dimensional Intelligent Calculation" commercial software for calculating the molecular weight of biological macromolecules.
[0016] The specific test method is:
[0017] A.1 Test steps
[0018] A.1.1 Viscosity test
[0019] Choose a suitable diameter (so that the data does not exceed the test range of the rheometer and a stable signal can be obtained), such as a 25 mm parallel plate (PP25). During the test, the test is protected by nitrogen purge through the temperature control hood (H-PTD200 hood with peltierheating / cooling); in addition, a thin layer of low-viscosity silicone oil (viscosity of about 10 mPa·s) is added to the edge of the sample and the parallel plate to prevent the sample from absorbing water vapor during the test.
[0020] The steady-state test mode was adopted: the experimental temperature was 30 °C, the shear rate was scanned from low to high, and the shear rate range was: 10 -3 s -1 ~10 3 s -1. Record the viscosity value of the platform curve.
[0021] A.1.2 Storage modulus and loss modulus test
[0022] Sample placement and test preparation are the same as B.4.1
[0023] The linear dynamic elastic test mode was used, that is, the strain amplitude of the oscillation mode was controlled below 10% to ensure that the test results were within the frequency scanning range (1×10 2 rad / s~6.81×10 -2 rad / s) internal storage modulus ( ) and loss modulus ( ) is linear. The test was carried out at a relative humidity of 30% to 40%.
[0024] Frequency sweeps were performed at the following temperatures (0 ℃, 10 ℃, 20 ℃ and 30 ℃) to obtain the storage modulus and loss modulus curves of the samples at different temperatures. The test time for each test was guaranteed to be within 1.5 h.
[0025] A.2 Calculation
[0026] B.5.1 Confirmation of system establishment
[0027] When using the AmimCl solvent system, the literature [1] Verification experimental studies show that the Huggins parameter K H The value is about 0.1, which indicates that the solvent is a good solvent for silk protein. The specific calculation is based on formulas (1) to (3).
[0028] a) By measuring the viscosity of the solution and solvent at different concentrations at the same temperature, the specific viscosity is calculated according to formula (1).
[0029] …………(1)
[0030] In the formula,
[0031] - viscosity;
[0032] - Viscosity of the solution;
[0033] - Viscosity of the solvent;
[0034] b) Calculate the intrinsic viscosity according to formula (2) based on the concentration approaching the limit value.
[0035] …………(2)
[0036] In the formula,
[0037] [η] —— intrinsic viscosity;
[0038] ——Specific viscosity;
[0039] C is the mass concentration of the solution.
[0040] c) Calculate the Huggins parameter from the viscosity of the solution according to formula (3):
[0041] …………(3)
[0042] In the formula,
[0043] ——Specific viscosity;
[0044] C ——mass concentration of solution;
[0045] [ ] —— intrinsic viscosity;
[0046] A —— viscosity of solvent;
[0047] K H ——Huggins parameters.
[0048] Note 1: This document verifies the Huggins parameters using the AmimCl solvent system. It is about 0.1, which meets the requirements and does not need to be verified;
[0049] Note 2: If other solvent systems are used, verification is required.
[0050] B.5.2 Molecular weight fitting calculation
[0051] Import the measured rheological data and viscosity data into Favorsun SmartMolFit "multi-directional intelligent calculation" commercial software for calculating the molecular weight of biomacromolecules to calculate the number average molecular weight and weight average molecular weight. Alternatively, calculate according to formulas (4) to (10).
[0052] a) Storage modulus and loss modulus: In the instrument parameter setting, strain ,stress , is the angular frequency, is the stress leading phase angle. The stress is expanded into The stress-strain relationship can be further described by a storage modulus that is in phase with the strain ( ) and a phase difference with the strain Energy loss modulus ( ) is expressed as follows, such as formula (4) to formula (6):
[0053] …………(4)
[0054] …………(5)
[0055] …………(6)
[0056] in, Storage modulus reflects the energy stored in the sample after applied strain. Loss modulus reflects the energy loss during the response process. In the dynamic shear method, the rheometer can give Storage modulus and Loss modulus versus alternating shear frequency The storage modulus and loss modulus can be directly obtained from the instrument test results.
[0057] b) Calculation of displacement factor: Calculate the displacement factor using the viscosity curve of the sample at different temperatures in test step B.4.1 ( ), calculated according to formula (7):
[0058] In the formula,
[0059] ——Specific viscosity;
[0060] C ——mass concentration of solution;
[0061] [ ] —— intrinsic viscosity;
[0062] A —— viscosity of solvent;
[0063] K H ——Huggins parameters.
[0064] Note 1: This document verifies the Huggins parameters using the AmimCl solvent system. It is about 0.1, which meets the requirements and does not need to be verified;
[0065] Note 2: If other solvent systems are used, verification is required.
[0066] B.5.2 Molecular weight fitting calculation
[0067] Import the measured rheological data and viscosity data into Favorsun SmartMolFit "multi-directional intelligent calculation" commercial software for calculating the molecular weight of biomacromolecules to calculate the number average molecular weight and weight average molecular weight. Alternatively, calculate according to formulas (4) to (10).
[0068] a) Storage modulus and loss modulus: In the instrument parameter setting, strain ,stress , is the angular frequency, is the stress leading phase angle. The stress is expanded into The stress-strain relationship can be further described by a storage modulus that is in phase with the strain ( ) and a phase difference with the strain Energy loss modulus ( ) is expressed as follows, such as formula (4) to formula (6):
[0069] …………(4)
[0070] …………(5)
[0071] …………(6)
[0072] in, Storage modulus reflects the energy stored in the sample after applied strain. Loss modulus reflects the energy loss during the response process. In the dynamic shear method, the rheometer can give Storage modulus and Loss modulus versus alternating shear frequency The storage modulus and loss modulus can be directly obtained from the instrument test results.
[0073] b) Calculation of displacement factor: Calculate the displacement factor using the viscosity curve of the sample at different temperatures in test step B.4.1 ( ), calculated according to formula (7):
[0074] ………………(7)
[0075] In the formula,
[0076] ——displacement factor;
[0077] ——Viscosity of the sample at different temperatures, Pa•s;
[0078] ——Viscosity of the sample at 30 ℃, Pa•s;
[0079] ——Different test temperatures, °C;
[0080] ——30 ℃;
[0081] c) Molecular weight distribution curve fitting:
[0082] Assuming the probability density of silk protein molecules with molecular weights ranging from 10 kDa to 40 kDa in the solution, substitute it into the Rouse model and obtain the fitting curve according to formulas (8) to (10):
[0083]
[0084]
[0085]
[0086] In the formula,
[0087] ——Storage modulus;
[0088] ——Loss modulus
[0089] ——Solution density;
[0090] ——gas constant (8.31);
[0091] ——Absolute temperature during test
[0092] M i ——The molecular weight of a silk protein molecule, here it is 10 kDa~40 kDa
[0093] f(i) is the molecular weight M i The probability density of
[0094] 0 ——Viscosity of polymer solution;
[0095] ——relaxation time of the pth relaxation mode of a polymer chain with molecular weight M
[0096] d) Molecular weight calculation: Using the displacement factor obtained by formula (7) , translate the test results of test step B.4.2, translate the test data at low temperature to obtain high-frequency area data, and obtain the main curve; compare the main curve with the fitting curve obtained in step B.5.2 c), and iterate continuously until the main curve and the fitting curve reach optimal coincidence, that is, "introduce a dynamic convergence factor in the optimization process, and improve the global optimization ability of the optimization algorithm through an adaptive weight strategy. As the number of iterations increases, the value of the dynamic convergence factor gradually decreases to 0. When the current number of iterations reaches the maximum number of iterations, the convergence process terminates, which is the optimal coincidence". This assumed value is the true probability density of silk protein with a molecular weight of 10 kDa to 40 kDa in the solution. Further calculations based on this probability density can obtain the number average molecular weight, weight average molecular weight and molecular weight distribution index of silk protein. The calculation formula is:
[0097]
[0098]
[0099] The above process can also be found in the description of molecular weight testing and AI calculation in WO2023 / 024607.
[0100] S2: Preparation of silk protein-cellulose gel: dissolve cellulose in water to fully swell it, add the cellulose aqueous solution to the silk protein aqueous solution prepared in step S1, mix them, and then ultrasonically treat them in an ice bath. Then adjust the osmotic pressure to 250-350mOsm / L with an osmotic pressure regulator, stir the mixed solution evenly, and place it in an oven for gelation.
[0101] Preferably, in S1, the molecular weight of the silk protein is 10-200 KD.
[0102] Preferably, in S2, the mass ratio of the silk protein to the cellulose is 1:1-10:1.
[0103] Preferably, in S2, the mass fraction of the silk protein is 0.5-5%.
[0104] Preferably, in S2, the mass fraction of cellulose is 0.05-5%.
[0105] Preferably, in S2, the cellulose swelling time is 6 to 26 hours.
[0106] Preferably, in S2, the conditions for ultrasonic treatment are: ultrasonic power of 200-500 W, ice bath temperature of 4-10° C., and ultrasonic time of 0.1-1 h.
[0107] Preferably, in S2, the osmotic pressure regulator is a 0.9 wt% sodium chloride solution or a phosphate buffer solution (PBS).
[0108] Preferably, in S2, the oven temperature is 70-80°C, and the gelation time is 8-24h.
[0109] The present invention also provides a method for preparing a silk protein filler containing hydroxyapatite microspheres for injection, which specifically comprises the following steps:
[0110] S3: Disperse the hydroxyapatite microspheres in a 2wt% silk protein solution, stir at 200 rpm at room temperature, then take out the microspheres and dry them, then disperse them in a 0.5wt% cellulose solution, stir at 200 rpm at room temperature, then take out the microspheres and dry them, and repeat several times;
[0111] Preferably, in S3, the particle size of the hydroxyapatite microspheres is 20-45 μm.
[0112] After S3 treatment, the surface of the microspheres is covered with a layer of polymer composite film, and the surface micropores disappear, which is equivalent to layer-by-layer self-assembly.
[0113] S4: Degassing the modified microspheres and silk protein-cellulose gel by negative pressure stirring, sterilizing by high-pressure steam, and filling them into prefilled syringes to obtain a silk protein mixed gel containing hydroxyapatite microspheres for injection.
[0114] Preferably, in S4, the mass ratio of hydroxyapatite microspheres to the volume of silk protein solution is 1-20 g:100 mL.
[0115] Preferably, in S4, the mass ratio of hydroxyapatite microspheres to the volume ratio of cellulose solution is 1-20 g:100 mL.
[0116] Preferably, in S4, the mass ratio of hydroxyapatite microspheres to silk protein-cellulose gel is 1:10 to 1:1.
[0117] Preferably, in S4, the stirring conditions of the hydroxyapatite microspheres and the silk protein-cellulose gel are 2-10 kPa, 500-2500 rpm, and 0.1-2 hours.
[0118] Preferably, in S4, the temperature of high pressure steam sterilization is 115-125° C. and the time is 15-30 minutes.
[0119] The hydroxy cellulose or carboxyl cellulose is selected from one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose and hydroxyethyl cellulose.
[0120] A silk protein composite hydroxyapatite microsphere filler for injection is obtained by adopting the preparation method.
[0121] The above-mentioned injectable silk protein composite hydroxyapatite microsphere filler is used as a medical beauty filler, such as for the face or for one or more of the tear grooves, crow's feet, temples, nose, chin, nasolabial folds, mouth corners, and forehead and temporal areas.
[0122] The beneficial effects achieved by the present invention are as follows:
[0123] The present invention provides a method for preparing a silk protein composite hydroxyapatite filler with different molecular weights. The hydrophobic interaction between hydroxypropyl methylcellulose molecules, carboxymethyl cellulose or hydroxyethyl cellulose and silk protein molecules after heating induces the silk protein molecular chain to change from random curling to β-folding. This secondary structural transformation can form a small and uniform β-folding structure inside the silk protein, and it is precisely the β-folding structure that is uniformly distributed in the entire gel system as a cross-linking site to form a three-dimensional fiber network structure, thereby avoiding the problem of skin allergies caused by adding chemical cross-linking agents; the surface of the hydroxyapatite microspheres is first covered with a layer of silk-cellulose film through a layer-by-layer self-assembly method to increase the microspheres. The surface of the ball is hydrophilic, and then evenly stirred with the silk protein-cellulose gel, the hydroxyapatite microspheres can be evenly dispersed in the gel system, avoiding facial redness, nodules and other problems caused by the microspheres clumping together. The molecular weight of the silk protein is determined by combining the AI algorithm with the rheological properties of the silk protein. Silk proteins with different molecular weights have different degrees of elastic modulus and complex viscosity, and the silk protein mixed gel is applied to different filling parts and layers to meet different beauty needs. The above-mentioned added ingredients have good biocompatibility, which can reduce the rejection of fillers in the body and avoid allergic and red and swollen skin problems after filling. BRIEF DESCRIPTION OF THE DRAWINGS
[0124] Figure 1 It is the rheological property of the products prepared in Examples 1 to 3 at 0.7 Hz.
[0125] Figure 2 These are the in vitro degradation performance results of the silk protein-cellulose gel in Examples 1 to 3.
[0126] Figure 3 This is a comparison of the gel states of the silk protein-cellulose gel prepared in Example 1 (left) and the silk protein gel prepared in Comparative Example 1 when placed in an oven for 8 hours (right).
[0127] Figure 4 This is the particle size distribution diagram of the hydroxyapatite microspheres in Example 1.
[0128] Figure 5 This is a scanning electron microscope comparison of the microspheres after layer-by-layer self-assembly in Example 1 (left) and the microspheres in Comparative Example 2 (right).
[0129] Figure 6It is a comparison chart of the pushing force of the products prepared in Example 1 and Comparative Example 2.
[0130] Figure 7 This is a hematoxylin-eosin staining picture of the products prepared in Examples 1 to 3 one month after implantation.
[0131] Figure 8 This is the immunohistochemical staining of type I collagen and type III collagen of the products prepared in Examples 1 to 3 one month after implantation. DETAILED DESCRIPTION
[0132] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. In addition, it should be understood that after reading the contents disclosed in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention.
[0133] Example 1
[0134] S1: Preparation of silk protein solution: mulberry silk is degummed, dissolved, clarified and filtered, purified and desalted, and concentrated to obtain silk protein, which is then dissolved in ionic liquid and tested on a MCR301 rotational rheometer. The data curves at multiple test temperatures are measured, and then the data are modeled using the rouse model. The physical parameters required for the model are measured, and then the nonlinear model is fitted using the AI algorithm to screen out silk proteins with a molecular weight of 10~50KD. The mass fraction of the silk protein aqueous solution is 10%.
[0135] S2: Preparation of silk protein-hydroxypropyl methylcellulose gel:
[0136] a) Weigh 1g of hydroxypropyl methylcellulose (Anhui Shanhe Pharmaceutical Excipients Co., Ltd., substituted type: 1828) and dissolve it in 20mL of water. Let it swell for 24h to obtain a 5% hydroxypropyl methylcellulose aqueous solution;
[0137] b) Weigh 1.01 g of disodium hydrogen phosphate and 0.25 g of sodium dihydrogen phosphate and dissolve them in 100 mL of water to obtain a 0.1 M PBS solution.
[0138] c) Weigh 20 g of the solution prepared in step S1, 10 g of 5% hydroxypropyl methylcellulose aqueous solution and 10 g of 0.1 M PBS solution, mix well with 60 g of water, perform ice bath ultrasound at 300 W for 0.5 h, and place in a 70°C oven for 8 h.
[0139] S3: Preparation of layer-by-layer self-assembled hydroxyapatite microspheres:
[0140] a) Weigh 3 g of hydroxyapatite microspheres (particle size 20-45 μm, Sigma), dissolve in 100 mL of 2 wt% silk protein solution, stir at 200 rpm for 3 h at room temperature, and concentrate the reactant to dryness;
[0141] b) Dissolve the concentrated and dried sample in 100 mL of 0.5 wt% cellulose solution, stir at 200 rpm at room temperature for 1 hr, and concentrate the reactant to dryness; repeat steps a) and b) 3 times.
[0142] S4: Preparation of injectable silk protein composite hydroxyapatite microsphere facial filler:
[0143] The modified hydroxyapatite microspheres were added to 7 g of the gel prepared in step S2, stirred at a rotation speed of 2300 rpm and a vacuum degree of 2 kPa for 30 minutes, aseptically filled into a 1 mL prefilled syringe, and then sterilized with high-pressure steam at a temperature of 121° C. for 30 minutes to obtain a silk protein filler containing hydroxyapatite microspheres.
[0144] Example 2
[0145] S1: Preparation of silk protein solution: the same as step S1 in Example 1. Silk protein with a molecular weight of 50 KD to 100 KD was screened out by combining AI algorithm with rheological properties of silk protein, and the mass fraction of the silk protein aqueous solution was 10%.
[0146] S2: Preparation of silk fibroin-carboxymethyl cellulose gel:
[0147] a) Weigh 0.8 g of carboxymethyl cellulose and hydroxypropyl methylcellulose and dissolve them in 16 mL of water, and fully swell them for 24 hours to obtain a 5% by mass hydroxypropyl methylcellulose aqueous solution;
[0148] b) Weigh 0.808 g of disodium hydrogen phosphate and 0.2 g of sodium dihydrogen phosphate and dissolve them in 80 mL of water to obtain a 0.1 M PBS solution;
[0149] c) Weigh 10 g of the solution prepared in step S1, 5 g of a 5% aqueous solution of carboxymethylcellulose / hydroxypropylmethylcellulose and 5 g of a 0.1 M PBS solution, mix well with 30 g of water, perform ice bath ultrasound at 280 W for 0.5 h, and place in a 70° C. oven for 8 h.
[0150] S3: Preparation of layer-by-layer self-assembled hydroxyapatite microspheres:
[0151] a) Weigh 3 g of hydroxyapatite microspheres (particle size 20-45 μm), dissolve them in 100 mL of 2 wt% silk protein solution, stir at 200 rpm for 2 h at room temperature, and concentrate the reactants to dryness;
[0152] b) Dissolve the concentrated and dried sample in 100 mL of 0.5 wt% cellulose solution, stir at 200 rpm for 0.5 h at room temperature, and concentrate the reactant to dryness; repeat steps a) and b) 3 times.
[0153] S4: Preparation of silk protein composite hydroxyapatite microsphere filler for injection:
[0154] The modified hydroxyapatite microspheres were added to 7 g of the gel prepared in step S2, stirred at a rotation speed of 2000 rpm and a vacuum degree of 2 kPa for 25 minutes, aseptically filled into a 1 mL prefilled syringe, and then sterilized with high-pressure steam at a temperature of 121° C. for 30 minutes to obtain a silk protein filler containing hydroxyapatite microspheres.
[0155] Example 3
[0156] S1: Preparation of silk protein solution: the same as step S1 in Example 1. Silk protein with a molecular weight of 100 KD to 150 KD was screened out by combining AI algorithm with rheological properties of silk protein, and the mass fraction of the silk protein aqueous solution was 10%.
[0157] S2: Preparation of silk fibroin-hydroxypropyl methylcellulose gel:
[0158] a) Weigh 1 g of hydroxypropyl methylcellulose and dissolve it in 20 mL of water, and fully swell it for 24 hours to obtain a 5% hydroxypropyl methylcellulose aqueous solution;
[0159] b) Weigh 0.808 g of disodium hydrogen phosphate and 0.2 g of sodium dihydrogen phosphate and dissolve them in 80 mL of water to obtain a 0.1 M PBS solution;
[0160] c) Weigh 40 g of the solution prepared in step S1, 10 g of a 5% hydroxypropyl methylcellulose aqueous solution and 10 g of a 0.1 M PBS solution, mix them evenly with 40 g of water, perform ice bath ultrasound at 280 W for 0.5 h, and place them in a 70° C. oven for 8 h.
[0161] S3: Preparation of layer-by-layer self-assembled hydroxyapatite microspheres:
[0162] a) Weigh 3 g of hydroxyapatite microspheres (particle size 20-45 μm), dissolve them in 100 mL of 2 wt% silk protein solution, stir at 200 rpm for 4 h at room temperature, and concentrate the reactants to dryness;
[0163] b) Dissolve the concentrated and dried sample in 100 mL of 0.5 wt% cellulose solution, stir at 200 rpm for 2 h at room temperature, and concentrate the reactant to dryness; repeat steps a) and b) 3 times.
[0164] S4: Preparation of silk protein composite hydroxyapatite microsphere filler for injection:
[0165] The concentrated hydroxyapatite microspheres were added to 7 g of the gel prepared in step S2, stirred at a rotation speed of 1800 rpm and a vacuum degree of 5 kPa for 35 minutes, aseptically filled into a 1 mL prefilled syringe, and then sterilized with high-pressure steam at a temperature of 121° C. for 30 minutes to obtain a silk protein filler containing hydroxyapatite microspheres.
[0166] Example 4
[0167] S1: Preparation of silk protein solution: the same as step S1 in Example 1. Silk protein with a molecular weight of 100 KD to 150 KD was screened out by combining AI algorithm with rheological properties of silk protein, and the mass fraction of the silk protein aqueous solution was 10%.
[0168] S2: Preparation of silk fibroin-hydroxypropyl methylcellulose gel:
[0169] a) Weigh 1 g of hydroxypropyl methylcellulose and dissolve it in 20 mL of water, and fully swell it for 24 hours to obtain a 5% hydroxypropyl methylcellulose aqueous solution;
[0170] b) Weigh 0.808 g of disodium hydrogen phosphate and 0.2 g of sodium dihydrogen phosphate and dissolve them in 80 mL of water to obtain a 0.1 M PBS solution;
[0171] c) Weigh 40 g of the solution prepared in step S1, 10 g of a 5% hydroxypropyl methylcellulose aqueous solution and 10 g of a 0.1 M PBS solution, mix them evenly with 40 g of water, perform ice bath ultrasound at 280 W for 0.5 h, and place them in a 70° C. oven for 8 h.
[0172] S3: Preparation of layer-by-layer self-assembled hydroxyapatite microspheres:
[0173] a) Weigh 3 g of hydroxyapatite microspheres (particle size 40-60 μm), dissolve them in 100 mL of 2 wt% silk protein solution, stir at 200 rpm for 4 h at room temperature, and concentrate the reactants to dryness;
[0174] b) Dissolve the concentrated and dried sample in 100 mL of 0.5 wt% cellulose solution, stir at 200 rpm for 2 h at room temperature, and concentrate the reactant to dryness; repeat steps a) and b) 5 times.
[0175] S4: Preparation of silk protein composite hydroxyapatite microsphere filler for injection:
[0176] The concentrated hydroxyapatite microspheres were added to 7 g of the gel prepared in step S2, stirred at a rotation speed of 1800 rpm and a vacuum degree of 5 kPa for 35 minutes, aseptically filled into a 1 mL prefilled syringe, and then sterilized with high-pressure steam at a temperature of 121° C. for 30 minutes to obtain a silk protein filler containing hydroxyapatite microspheres.
[0177] Comparative Example 1 - No Cellulose Composite Filler Added
[0178] The gelation rate of the gel without cellulose is slower, the gel is obviously loose, and there is more water on the surface. Figure 3 As shown, the filler preparation process is as follows:
[0179] S1: Preparation of silk protein solution: the same as step S1 in Example 1. Silk protein with a molecular weight of 10-50 KD was screened out by combining AI algorithm with rheological properties of silk protein, and the mass fraction of the silk protein aqueous solution was 10%.
[0180] S2: Preparation of silk protein gel:
[0181] a) Weigh 0.808 g of disodium hydrogen phosphate and 0.2 g of sodium dihydrogen phosphate and dissolve them in 80 mL of water to obtain a 0.1 M PBS solution;
[0182] b) Weigh 10 g of the solution prepared in step S1 and 5 g of 0.1 M PBS solution, mix them evenly with 35 g of water, perform ice bath ultrasound at 300 W for 0.5 h, and place them in an oven at 70 °C for 24 h.
[0183] S3: Preparation of silk protein filler containing hydroxyapatite microspheres for injection:
[0184] a) Weigh 3 g of hydroxyapatite microspheres, dissolve them in 100 mL of 2 wt% silk protein solution, stir at 200 rpm at room temperature overnight, and concentrate the reactant;
[0185] b) Dissolve the concentrated sample in 100 mL of 0.5 wt% cellulose solution and stir at 200 rpm at room temperature overnight to concentrate the reactant; repeat the above process three times.
[0186] S4: adding the concentrated hydroxyapatite microspheres to 7 g of the gel prepared in step S2, stirring for 30 minutes at a rotation speed of 2300 rpm and a vacuum degree of 2 kPa, aseptically filling into a 1 mL prefilled syringe, and then sterilizing with high-pressure steam at a temperature of 121° C. for 30 minutes to obtain a silk protein mixed gel containing hydroxyapatite microspheres.
[0187] Comparative Example 2-Hydroxyapatite without surface modification
[0188] from Figure 3It can be seen that the filler prepared by hydroxyapatite without layer-by-layer self-assembly modification has a large fluctuation in pushing force. This is mainly because the hydroxyapatite is unevenly dispersed and prone to agglomeration and precipitation. Therefore, the local hydroxyapatite concentration of the filler is inconsistent, resulting in large fluctuations in pushing force. After the hydroxyapatite microspheres are self-assembled layer by layer and then mixed with silk protein-cellulose gel, the mixed gel prepared has a smaller and more uniform pushing force, which shows that the hydroxyapatite microspheres are well dispersed in the gel.
[0189] The filler preparation test process is as follows:
[0190] S1: Preparation of silk protein solution: mulberry silk is degummed, dissolved, clarified and filtered, purified and desalted, and concentrated to obtain silk protein, which is then dissolved in ionic liquid and tested on a MCR301 rotational rheometer. The data curves at multiple test temperatures are measured, and then the data are modeled using the rouse model. The physical parameters required for the model are measured, and then the nonlinear model is fitted using the AI algorithm to screen out silk proteins with a molecular weight of 10~50KD. The mass fraction of the silk protein aqueous solution is 10%.
[0191] S2: Preparation of silk protein gel:
[0192] a) Weigh 0.808 g of disodium hydrogen phosphate and 0.2 g of sodium dihydrogen phosphate and dissolve them in 80 mL of water to obtain a 0.1 M PBS solution;
[0193] b) Weigh 10 g of the solution prepared in step S1 and 5 g of 0.1 M PBS solution, mix them evenly with 35 g of water, perform ice bath ultrasound at 300 W for 0.5 h, and place them in an oven at 70 °C for 24 h.
[0194] S3: Preparation of silk protein mixed gel containing hydroxyapatite microspheres for injection:
[0195] Weigh 3 g of hydroxyapatite microspheres, add them to 7 g of the gel prepared in step S2, stir for 30 minutes at a rotation speed of 2300 rpm and a vacuum degree of 2 kPa, aseptically fill them in a 1 mL prefilled syringe, and then sterilize them with high-pressure steam at a temperature of 121° C. for 30 minutes to obtain a silk protein mixed gel containing hydroxyapatite microspheres.
[0196] Rheological properties test
[0197] In this experimental example, the mixed gels prepared in Examples 1 to 3 were subjected to rheological tests. The specific method is as follows: a 25 mm parallel plate (PP25) was selected, the sample was extruded onto the plate, and a thin layer of low-viscosity silicone oil was dripped on the edge of the sample and the parallel plate to prevent the sample from absorbing water vapor during the test. At 25 °C and a deformation pressure of 0.1%, a frequency sweep was performed to obtain the modulus and viscosity of each sample at 0.7 Hz, and each sample was tested 3 times in parallel.
[0198] Figure 1 The elastic modulus and complex viscosity data of the mixed gel prepared in Examples 1 to 3 at 0.7 Hz show that the larger the molecular weight of the silk protein, the higher the elastic modulus and complex viscosity of the filler, the better the support and plasticity of the filler, the better the mechanical properties, the less likely it is to be displaced, and it is suitable for deeper filling.
[0199] Degradation rate test
[0200] This experimental example measures the in vitro degradation performance of the mixed gels prepared in Examples 1 to 3. The specific method is as follows: Prepare a citric acid buffer solution: Take a 1000 mL volumetric flask, dissolve 21 g of citric acid monohydrate in 500 mL of water, add 200 mL of 1 mol / L sodium hydroxide solution, and then dilute with water to full scale. Mix 40.4 mL of the solution with 59.6 mL of 0.1 mol / L hydrochloric acid solution to prepare a citric acid buffer solution. Take 20 mL of it, add 1 g of the mixed gel prepared in Examples 1 to 3, respectively, place it in a 37°C water bath environment, weigh the mass loss of the filler at 1 day, 7 days, 4 weeks, 8 weeks, and 12 weeks, and convert this mass loss into the degradation rate of the filler.
[0201] Figure 2 The in vitro degradation curves of the mixed gels prepared in Examples 1 to 3 show that the larger the molecular weight of the silk protein, the longer the degradation period of the filler and the slower the degradation rate.
[0202] Push force test
[0203] In this experimental example, the pushing force of the mixed gel prepared in Example 1 and Comparative Example 2 was measured. The specific method was as follows: a 1 mL syringe containing the mixed gel was placed on a pushing force measuring instrument, the push rod was pushed at a speed of 30 mm / min, and the pushing force curve within a pushing displacement of 2 mm was recorded.
[0204] Figure 3The pushing force curves of the mixed gels prepared in Example 1 and Comparative Example 2 show that the mixed gels prepared by mixing hydroxyapatite microspheres with silk protein-cellulose gel after hierarchical self-assembly have smaller and more uniform pushing force, which indicates that the hydroxyapatite microspheres are well dispersed in the gel.
[0205] Experimental Example 4-Animal Experiment
[0206] The mixed gel obtained in Examples 1 to 3 was implanted subcutaneously on the back of New Zealand white rabbits, 0.1 mL at each implantation point, and the skin reaction at the implantation point was observed at 1 week, 2 weeks, 1 month, and 3 months after implantation. The rabbits were killed at 3 months, and samples were taken and sliced for hematoxylin-eosin staining and collagen type I and type III immunohistochemical staining.
[0207] The results showed that within 3 months, no abnormalities such as redness, swelling, and erythema were found on the skin surface and the inner side of the skin. Hematoxylin-eosin staining showed no abnormalities such as inflammatory cell infiltration and fibrous cysts, which proved that the filler had good biocompatibility. Immunohistochemical staining and quantitative results showed that the higher the molecular weight of silk protein, the more type I and type III collagen secretion, as shown in Table 1. High molecular weight is conducive to deep filling, promoting collagen regeneration and tissue reconstruction.
[0208] Table 1 Quantitative table of immunohistochemical staining of type I collagen and type III collagen 1 month after implantation of the mixed gel of Examples 1 to 3
[0209]
[0210] in addition, Figure 4 A particle size analysis was conducted on the hydroxyapatite microspheres used, and the results showed that the median particle size was around 34 microns, microspheres with a particle size of 20-45 microns accounted for more than 94.6%, and microspheres with a particle size below 20 microns accounted for less than 2.2%, which avoided the risk of small-particle microspheres easily triggering macrophage storms.
[0211] Figure 5 Through scanning electron microscopy, it can be seen that after the microspheres are self-assembled layer by layer, the surface is covered with a layer of silk protein-cellulose film, which makes the surface of the microspheres smoother and avoids the formation of granulomas after injection.
[0212] Figure 6 This shows that the pushing force curve of the microspheres after layer-by-layer self-assembly is smoother than that of the unassembled microspheres after mixing with the gel, which also proves that the microspheres are more evenly dispersed in the gel matrix after layer-by-layer self-assembly.
[0213] Figure 7It was shown that after implantation of the injectable silk protein composite hydroxyapatite microsphere filler, no tissue necrosis was observed, only a very small amount of macrophage infiltration was observed, and the biological safety was good; new blood vessel formation was visible and supported by fibroblasts.
[0214] Figure 8 It shows that after one month of subcutaneous implantation, some collagen fibers were generated. The collagen fibers were distributed in the gel gaps and the surface of the microspheres, and type I and type III collagen were arranged in parallel between the microsphere gaps. The higher the molecular weight of silk protein, the larger the collagen area (brown area) of the tissue around the implant after the injection of silk protein composite hydroxyapatite microsphere facial filler. The above results prove that the injection of silk protein composite hydroxyapatite microsphere facial filler can be used as a soft tissue filler for subcutaneous implantation, with good biocompatibility and ability to promote collagen regeneration.
[0215] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a silk protein composite hydroxyapatite microsphere filler for injection, characterized in that: The following steps are involved: S1: Preparation of silk protein solution: The degummed silk is dissolved and purified to obtain silk protein, and silk proteins of different molecular weights are screened out through membranes with different molecular weight cut-offs; S2: Physical gelation of silk protein: dissolving a physical crosslinking agent in water to fully swell, wherein the physical crosslinking agent is hydroxycellulose or carboxyl cellulose or a corresponding derivative, adding hydroxycellulose or carboxyl cellulose or a corresponding derivative aqueous solution to the silk protein aqueous solution prepared in step S1, adjusting the osmotic pressure, and then stirring the mixed solution evenly, placing it in an oven for gelation, and obtaining a silk protein-cellulose gel; S3: Preparation of hydroxyapatite microspheres modified by layer-by-layer self-assembly: Disperse the hydroxyapatite microspheres in the silk protein solution prepared in step S1, stir at room temperature, then take out the microspheres and dry them; then dissolve them in the cellulose solution, stir at room temperature, then take out the microspheres and dry them; repeat 3 to 5 times; S4: Preparation of silk protein composite hydroxyapatite microsphere filler for injection: degassing the modified hydroxyapatite microspheres and the silk protein-cellulose gel prepared in step S2 by negative pressure stirring, sterilizing them with high-pressure steam, and aseptically filling them in a prefilled syringe to obtain a silk protein composite hydroxyapatite microsphere filler for injection; During the whole preparation process, no additional chemical crosslinking agent or photoinitiator needs to be added, and no photocrosslinking or radiation crosslinking is required.
2. The method for preparing the silk protein composite hydroxyapatite microsphere filler for injection according to claim 1, characterized in that: The step S1 comprises the following steps: The dried degummed silk is dissolved in a lithium bromide aqueous solution at a mass-to-volume ratio of less than or equal to 1:1, and the silk protein is fully dissolved in a water bath at 25-100°C for 10-120 minutes to obtain a mixed solution containing silk protein and a small amount of insoluble particles; the mixed solution is filtered out with a filter bag to remove insoluble particle impurities to obtain a clarified lithium bromide protein solution; the clarified solution is diluted with one times of pure water and passed into a purification system for desalination, and the solution is collected after desalination for later use; the purified silk protein aqueous solution is dried in a flat dish, and the mass concentration of the silk protein aqueous solution is measured by the mass difference method to be 1-10%, and molecular weight screening: silk proteins of different molecular weights are screened out by membranes with different molecular weight cutoffs.
3. The method for preparing the silk protein composite hydroxyapatite microfiller for injection according to claim 1, characterized in that: Step S2 The method comprises the following steps: weighing hydroxy cellulose and dissolving it in water to fully swell it for 10 to 30 hours; weighing sodium dihydrogen phosphate and disodium hydrogen phosphate and dissolving them in water, mixing and stirring the silk protein solution, the hydroxy cellulose aqueous solution, the sodium dihydrogen phosphate and disodium hydrogen phosphate solution with a certain amount of water evenly, placing the solution in an oven at 70 to 80° C. for gelation for 6 to 30 hours, and finally, the mass concentration of the silk protein aqueous solution is 0.5 to 10%, the mass concentration of the hydroxy cellulose aqueous solution is 0.1 to 10%, and the molar mass concentration of the sodium dihydrogen phosphate and the disodium hydrogen phosphate is 0.2 to 1M.
4. The method for preparing the silk protein composite hydroxyapatite microsphere filler for injection according to claim 1, characterized in that: The step S3 comprises the following steps: dispersing hydroxyapatite microspheres in a 0.5-5wt% silk protein solution, stirring at room temperature for 1-5h, then taking out the microspheres and drying them at 50-90°C for 0.5-3h; then dissolving them in a 0.2-1wt% cellulose solution, stirring at room temperature for 1-5h, then taking out the microspheres and drying them at 50-90°C for 0.5-3h; and repeating 3-5 times.
5. The method for preparing the silk protein composite hydroxyapatite microsphere filler for injection according to any one of claims 1 to 4, characterized in that: The hydroxy cellulose or carboxyl cellulose is selected from one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose and hydroxyethyl cellulose; the degummed silk is from one or more of mulberry silk, tussah silk and spider silk.
6. The method for preparing the silk protein composite hydroxyapatite microsphere filler for injection according to any one of claims 1 to 4, wherein the osmotic pressure is adjusted to 250-350 mOsm / L using an osmotic pressure regulator.
7. The method for preparing the silk protein composite hydroxyapatite microsphere filler for injection according to claim 5, wherein the osmotic pressure is adjusted to 250-350 mOsm / L using an osmotic pressure regulator.
8. A silk protein composite hydroxyapatite microsphere filler for injection, characterized in that: The preparation method is adopted according to any one of claims 1 to 7.
9. A use of the silk protein composite hydroxyapatite microsphere filler for injection according to claim 8, characterized in that: Used in the preparation of medical fillers.
10. The use according to claim 9, characterized in that Used to prepare medical cosmetic fillers.
11. The use according to claim 9, characterized in that The medical filler is used for one or more of tear grooves, crow's feet, stretch marks, temples, nose, chin, nasolabial folds, mouth corners, forehead and temporal area, neck, and genitals.
12. The use according to claim 9, characterized in that The medical filler is used for filling and repairing skin tissue or soft tissue.
13. The use according to claim 9, characterized in that The medical filler is used for filling and repairing the face, trunk or limbs.
Citation Information
Patent Citations
Multi-crosslinked gel system and product, preparation method and application thereof
CN116284886A
Injection filler and redissolving method thereof
CN116808290A
Method for calculating molecular weight of bio-macromolecular material on the basis of ai algorithm
WO2023024607A1
Preparation method of silk fibroin / hydroxyapatite / collagen composite porous stent
CN102321270A
Fibroin / cellulose derivative composite material and preparation method thereof
CN110144123A